2010
DOI: 10.3749/canmin.48.3.673
|View full text |Cite
|
Sign up to set email alerts
|

The Pyrochlore Supergroup of Minerals: Nomenclature

Abstract: A new scheme of nomenclature for the pyrochlore supergroup, approved by the CNMNC-IMA, is based on the ions at the A, B and Y sites. What has been referred to until now as the pyrochlore group should be referred to as the pyrochlore supergroup, and the subgroups should be changed to groups. Five groups are recommended, based on the atomic proportions of the B atoms Nb, Ta, Sb, Ti, and W. The recommended groups are pyrochlore, microlite, roméite, betafite, and elsmoreite, respectively. The new names are compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
324
0
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(348 citation statements)
references
References 75 publications
(91 reference statements)
9
324
0
15
Order By: Relevance
“…Liandratite shows a strong compositional similarity to the U-rich member of the pyrochlore group -uranopyrochlore (□,U 4+ ) 2 Nb 2 O 6 (O,OH,F) (Atencio et al 2010); however, it has a different U oxidation state. Unfortunately, to the author's knowledge, uranopyrochlore is still a rather theoretical member of the pyrochlore group because there is currently no species fulfilling the classification criteria proposed by Atencio et al (2010) for this mineral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liandratite shows a strong compositional similarity to the U-rich member of the pyrochlore group -uranopyrochlore (□,U 4+ ) 2 Nb 2 O 6 (O,OH,F) (Atencio et al 2010); however, it has a different U oxidation state. Unfortunately, to the author's knowledge, uranopyrochlore is still a rather theoretical member of the pyrochlore group because there is currently no species fulfilling the classification criteria proposed by Atencio et al (2010) for this mineral.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, to the author's knowledge, uranopyrochlore is still a rather theoretical member of the pyrochlore group because there is currently no species fulfilling the classification criteria proposed by Atencio et al (2010) for this mineral. Only one analysis in the literature satisfactorily meets the dominant valence rule regarding the U content in the A-site: analysis 9 from Chibiny (Chakhmouradian and Mitchell 2002).…”
Section: Introductionmentioning
confidence: 99%
“…According to the new nomenclature proposed by Atencio et al (2010), this elsmoreite reported by Williams et al (2005) is a specimen of the type hydrokenoelsmoreite. The hydrokenoelsmoreite discovered by Williams et al is nearly Al -free, whereas this hydrokenoelsmoreite from the Wazuka district contains a considerable amount of Al 2 O 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Of these three, only ferritungstite has been found at several locations in Japan (e.g., Matsubara et al, 1994, andTsunoda andShimizu, 1995), while the other two have not been reported to be found anywhere in Japan. Recently, however, Atencio et al (2010) proposed a new nomenclature scheme for the pyrochlore supergroup to which these three minerals belong, and these minerals were classified under a new group "hydrokenoelsmoreite." Thus, the present mineral (sample B) should be called hydrokenoelsmoreite.…”
Section: Hydrokenoelsmoreite [Sample B]mentioning
confidence: 99%
“…6, analysis 1 in Table 4) is not approved by the Commission on New Minerals Nomenclature and Classification of the International Mineralogical Assosiation. Moreover, this mineral is not listed among pyrochloresupergroup species for which analytical evidence is deemed adequate [25]. Consequently, hydroxyplumbobetafite is a potentially new mineral species that needs further investigations.…”
Section: T a B L Ementioning
confidence: 99%